Teachers motivational perception, motivational strategies and students academic achievements in Oman public schools - Al.Rawahi, Talal; Che.Hassan, Norlizah; Ismail, Asmah (2017)
In this study, the researcher has attempted to study the relationship, difference and the level of the teacher’s perception of the student’s motivation, different motivational strategies and the indicators of student’s academic achievements as seen in the Omani public school. The teacher’s perceptions regulated by the different reasons or causes which caused the lack of motivation amongst students, strategies used by the teachers and the various demographics like gender, class levels taught and their teaching experience. The schools selected from the Al Dakhelia Governorate, which is one of the 11 Governorates in Sultanate of Oman. Besides that, this survey correlational study used of (Hardre, 2008) teacher motivational perception (α=.75) and motivational Strategies (α=.84) questionnaires scores of Cronbach's Alpha. Pilot study have been conducted on 30 teachers which indicates scores of Cronbach's Alpha (α=.74). The results of this study showed that there was a moderate perception of students lacking motivation level (M=3.29, SD=.327), high level of strategies they used (M=4.38, SD=.974) and moderate student academic motivation(M=66.29, SD7.11). There is a positive and significant relationship between teachers' perception of motivation and student academic achievements (Male; r=.607 p=<0.05), Female (r=.418 p=<0.05). Likewise, there was a positive and significant relationship between teachers' motivational strategies and student academic achievements (Male; r=.285 p=<0.05), Female (r=.333 p=<0.05) which indicated a Low correlation, definite but small level. Finally, there were no differences used independent t test; p-value and one way ANOVA used due to the normal distribution of teacher motivational strategies mean score of gender (t=1.35, p>0.05), class level (F=.103, p<0.05) and teaching experience ( =.681, p>0.05) in the study. In the Other hands, there were significant differences of teacher motivational perception based on gender (t=2.163, p<0.05), class level (F=3.928, p=.202). The results of this study can be useful tools for the Omani school authorities, administrators, policymakers, and teacher educators for supporting the teachers in accurately developing student's motivations and motivational strategies for further students' academic achievements.